Perspectiva global de los combustibles sintéticos verdes: tecnologías, avances y desafíos en la transición energética - Orias-Rodríguez, Sebastián (2025)
Green synthetic fuels (from renewable sources and low emission) are produced from green hydrogen, combined with CO2 from sustainable sources or N2 from the air, using renewable energy. Various electrolyzer and reactor technologies enable the synthesis of products such as methane, methanol, ammonia, and even longer-chain hydrocarbons. Their main advantage with respect to the use of green hydrogen lies in the possibility of taking advantage of a large part of the existing infrastructure for its storage, transportation, and use. These characteristics position green synthetic fuels as a promising alternative for decarbonizing sectors that are difficult to decarbonize in industry and the global economy. This review outlines existing technologies to produce this type of fuel, focusing on their advantages, disadvantages, and applications at a global level. Understanding the development and expansion of these technologies is of great relevance for the creation and implementation of public policies in order to make informed decisions in the Latin American energy transition and promote the incorporation and innovation of these technologies.